A Practical Guide to Public Debt Dynamics, Fiscal Sustainability, and Cyclical Adjustment of Budgetary Aggregates - Escolano, Julio (Washington, D.C. : International Monetary Fund, 2010)
This paper presents a practical guide to public debt dynamics, fiscal sustainability, and cyclical adjustment of budgetary aggregates. The paper discusses fiscal formulas, which may be of practical use in fiscal analysis. The paper derives, respectively, the formulas for debt dynamics, and cyclical and inflation adjustment of budgetary aggregates. It discusses other relationships for special applications, and some practical implications and usage. The formulas related to debt dynamics are based on the assumption that changes in liabilities are the result of above-the-line budgetary operations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet